University ‘Values’ and Neoliberal Marketisation - Nesta Devine; Daniel Couch; Christoph Teschers (New Zealand Journal of Teachers' Work)
This editorial evaluates the potential impact of neoliberal marketisation on university values and culture drawing on the example of current bargaining between unions and university management in Aotearoa New Zealand.